2014
DOI: 10.1074/jbc.m113.536151
|View full text |Cite
|
Sign up to set email alerts
|

Competition through Dimerization between Antiapoptotic and Proapoptotic HS-1-associated Protein X-1 (Hax-1)

Abstract: Background:Hax-1 is a family of apoptotic regulators. The prototypical variant 1 has an antiapoptotic function. Results: Hax-1 variant 2 promotes cell death and can abrogate the protective effect of variant 1. Conclusion:The ratio of anti-and proapoptotic Hax-1 variants is likely to determine cell fate via sequestration or inactivation. Significance: Different splice variants of Hax-1 have opposing roles in regulating apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
(61 reference statements)
0
21
0
Order By: Relevance
“…All these results supported our conclusion that the mitochondrial Omi/HtrA2 promotes cardiomyocytes apoptosis again. However, the exact mechanism by which HAX-1 is degraded by Omi/HtrA2 during ischemia/reperfusion injury is the subject of ongoing investigation, although recent evidence suggests that HAX-1 can either function as an anti- or pro-apoptotic regulator, and in turn influence cell survival or death, through homo- or heterodimerization39. Future studies are therefore needed to determine whether Omi/HtrA2 helps balance the formation of HAX-1 homo- or heterodimers in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…All these results supported our conclusion that the mitochondrial Omi/HtrA2 promotes cardiomyocytes apoptosis again. However, the exact mechanism by which HAX-1 is degraded by Omi/HtrA2 during ischemia/reperfusion injury is the subject of ongoing investigation, although recent evidence suggests that HAX-1 can either function as an anti- or pro-apoptotic regulator, and in turn influence cell survival or death, through homo- or heterodimerization39. Future studies are therefore needed to determine whether Omi/HtrA2 helps balance the formation of HAX-1 homo- or heterodimers in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hax1 gene mutations in humans lead to severe neutropenia and symptoms of immunodeficiency, neurological disease and neurodevelopment abnormalities [2729]. In addition, Hax1 has multifunctional roles in other key cellular processes like calcium homeostasis and cell migration [27, 30]. Despite the reported prosurvival role of Hax1 various models [27], its function in cardiac cell apoptosis needs further elucidation.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike mouse Hax1, the human and rat genes have been shown to be heavily spliced, giving rise to variants that display differences in the NH2 terminus [32]. Interestingly, Koontz and Kontrogianni-Konstantopoulos have reported that Hax1 is a family of anti- and proapoptotic proteins that may regulate cell fate via homo- or heterodimerization [30]. …”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence intensity in each well is directly proportional to the ROS level within the cell cytosol. 58 In a separate experiment, the cells grown on the scaffolds for 48 h were stained with cell-permeant calcein AM dye (Life Technologies) to trace viability.…”
Section: Nanoscaffold/peptide Immune Toxicity Analysis Toward Mammalimentioning
confidence: 99%